Microstructural and excess conductivity properties of Y-123: effect of organic polymer chitosan inclusion - Yap, Siew Hong; Awang Kechik, Mohd Mustafa; Khoerunnisa, Fitri; Baqiah, Hussien; Chen, Soo Kien; Lim, Kean Pah; Shabdin, Muhammad Kashfi; Mohd Zaid, Mohd Hafiz; Yaakob, Yazid; Abdul Karim, Mohd Khalis; Humaidi, Syahrul; Shaari, Abdul Halim; et al. (Springer, 2024)
This research investigated the effect of chitosan as fine nucleation for the interactions among surface microstructure, secondary phases, and thermodynamic fluctuations of superconducting parameters during the superconducting transitions in YBa2Cu3O7-δ (Y-123) system. The study involved incorporating various low concentrations (0.0100 wt.% ≤ x ≤ 0.6000 wt.%) of chitosan (CHI) extracted from marine waste into the Y-123 matrix through a thermal treatment method annealed in an oxygen atmosphere. XRD results showed that all specimens crystallized into orthorhombic Y-123 as the main phase, with non-superconducting phases such as Y-211 and BaCuO2. These additions introduced different trends in grain degradation and appearance of nano-entities within the Y-123 matrix system. Investigations into the excess conductivity through DC resistivity measurements of these bulk granular specimens revealed a complete reduction in inter-layer coupling while preserving oxygen content and grain size. Furthermore, superconducting transition temperatures (Tc-onset, Tc-offset), superconducting transition width (ΔTc), and intergranular current density at zero temperature (Jc(0)) experienced significant improvements at lower concentrations, reaching an optimum at 0.0100 wt.%. The Jc(0) reached its peak value at 8.17 × 106 A/m2 for the specimen with 0.0100 wt.% CHI addition annealed in an oxygen atmosphere. This research underscores the potential of a sustainable approach involving the incorporation of low-concentration organic polymer (CHI), aligning with the principles of green materials and the advancement of superconductivity.